Pemberdayaan Masyarakat Melalui Diversifikasi Program Bank Sampah di Desa Rancakalong Sumedang - Indiriani, Ellya Dwi; Widiowati, Didiet (Lembaga Pengabdian kepada Masyarakat Universitas Langlangbuana, 2024)
Garbage is one of the problems that still needs to be addressed immediately, as is the case in Rancakalong Village. Waste processing has not yet been implemented because there is no TPA and TPS in the village. Most people only burn the rubbish they produce every day and it is not uncommon for them to just throw it carelessly throughout Rancakalong Village. This community service activity aims to provide public awareness about the importance of waste processing through the Community Empowerment through Waste Bank Diversification program. This activity uses participatory methods by involving the community as a whole, as well as extracting data through participatory observation, interviews, documentation studies and FGDs. The results of this activity are the formation of a Waste Bank TKM, increasing community knowledge and skills, as well as the impact of activities on the triple bottom line concept.